ANTIOXIDANT AND ANTIMICROBIAL POTENTIAL OF COCCINEA CORDIFOLIA - Roy, Saumendu Deb; Dash, Suvakanta; Chakraborty, Jashabir (International Journal of Research -GRANTHAALAYAH, 2018)
In the present study, Coccinea cordifolia root was extracted with various solvents according to their increasing order of polarity and the extracts were subjected to preliminary phytochemical investigation. The extracts were then subjected to antioxidant assay using FTC, TBA, DPPH and Reducing Power assay as models and Antimicrobial assay. The Methanolic extract of the plant root has shown good antioxidant and antimicrobial activity among the extracts under study. The findings of the study here justify the traditional claim against Coccinea cordifolia root.